New Trends in 3D Printing - V Shishkovsky, Igor (IntechOpen, 2016)
A quarter century period of the 3D printing technology development affords ground for speaking about new realities or the formation of a new technological system of digital manufacture and partnership. The up-to-date 3D printing is at the top of its own overrated expectations. So the development of scalable, high-speed methods of the material 3D printing aimed to increase the productivity and operating volume of the 3D printing machines requires new original decisions. It is necessary to study the 3D printing applicability for manufacturing of the materials with multilevel hierarchical functionality on nano-, micro- and meso-scales that can find applications for medical, aerospace and/or automotive industries. Some of the above-mentioned problems and new trends are considered in this book.